Terapi Spiritual Dalam Mengembangkan Penerimaan Diri Anak Terlantar di Panti Sosial Bina Remaja Taruna Jaya 1 - Muchammad Raafi Triyas Susandi; Ati Kusmawati (Institut Nalanda, 2024)
The phenomenon of abandoned children is increasingly widespread nowadays. The DKI Jakarta government has established an orphanage for the rehabilitation of abandoned children, namely the Bina Pemuda Taruna Jaya I Social Home. Another problem that arises for abandoned children living in the orphanage is poor self-acceptance due to the negative stigma attached to them and the problems they bring. The solution provided by the Taruna Jaya I Youth Development Social Home is to provide spiritual therapy services for social assistance residents. The aim of this research is to determine the implementation of spiritual therapy in developing self-acceptance in neglected children at the Bina Pemuda Taruna Jaya I Social Home. The research method used was descriptive qualitative using purposive sampling in determining informants. Researchers used observation, interview and documentation techniques in extracting data by analyzing data using the Miles and Huberman models. The results of the research show that the implementation of therapy carried out by social institutions starts from the diagnosis stage to deepen the data and problems of the inmates, the therapy stage uses religious values with paradoxical intention techniques to provide a sense of comfort and the follow-up stage provides supervision of the development of the inmates by providing activities. positive activities. The spiritual therapy carried out is known to be able to develop self-acceptance in neglected children. Supporting factors in implementing therapy are strong motivation to achieve the desired changes and an environment that provides encouragement. The inhibiting factor in implementing spiritual therapy is weak motivation due to boredom from activities that are repeated every day.